Evaluation of fracture resistance of endodontically treated teeth restored with prefabricated posts and composites with varying quantities of remaining coronal tooth structure Avaliação da resistência à fratura de dentes tratados endodonticamente restaurados com pinos pré-fabricados e resinas compostas variando o remanescente dentário coronal - Murilo Pereira de Melo; Accácio Lins do Valle; Jefferson Ricardo Pereira; Wellington Cardoso Bonachela; Luiz Fernando Pegoraro; Gerson Bonfante (University of São Paulo, 2005)
OBJECTIVES: The aim of this study was to evaluate the influence of remaining coronal tooth structure on endodontically treated teeth restored with prefabricated posts and two different composites for core build-up: dual-cured resin (Enforce Core) and light-cured resin (Z-250). METHODS: Fourty freshly extracted canines were endodontically treated and divided into four groups: Group I - teeth with 3mm remaining coronal structure, restored with Enforce Core; Group II - teeth with 3mm remaining coronal structure, restored with Z-250; Group III - teeth with no remaining coronal structure, restored with Enforce; Group IV - teeth with no remaining coronal structure, restored with Z-250. After restoration, the teeth were embedded in acrylic resin and the fracture resistance was measured on a universal testing machine at 45 degrees to the long axis of the tooth until failure. RESULTS: Data were analyzed by two-way analysis of variance, which showed significant differences between groups (p=0.00). The Tukey test did not show significant differences between specimens with and without remaining coronal structure. Conversely, significant difference was observed between groups with different core build-up. The highest values of fracture resistance were found in the group restored with light-cured resin. SIGNIFICANCE: The remaining coronal tooth structure did not influence the resistance of endodontically treated teeth; however, the change of core build-up was able to modify this resistence. O objetivo desta pesquisa foi avaliar a influência do remanescente dentário coronal de dentes tratados endodonticamente, restaurados com pinos pré-fabricados e duas resinas como núcleos de preenchimento, uma de presa dual (Enforce Core) e outra fotopolimerizável (Z-250). Foram utilizados 40 caninos superiores humanos extraídos, divididos em quatro grupos de 10 espécimes: Grupo l - com remanescente dentário coronal de 3mm e restaurados com Enforce Core; Grupo ll - com remanescente dentário coronal de 3mm e restaurado com Z-250; Grupo III - sem remanescente dentário coronal e restaurado com Enforce Core; Grupo IV - sem remanescente dentário coronal e restaurado com Z-250. Após restaurados, os dentes foram levados a uma Máquina de Ensaio Universal e submetidos a uma força de compressão à 45º até que ocorresse fratura da restauração. A análise dos resultados (ANOVA, p>0,05) mostrou não haver diferença estatisticamente significativa entre os dentes com e sem remanescente dentário coronal. Com relação ao material utilizado para o preenchimento coronário, constatou-se diferença significativa, sendo que os valores mais elevados de resistência à fratura foram encontrados no grupo restaurado com a resina fotopolimerizável.